Genetic and Virulence Profiles of Enteroaggregative Escherichia coli (EAEC) Isolated From Deployed Military Personnel (DMP) With Travelers' Diarrhea - Petro, Courtney D.; Duncan, Jeffrey K.; Seldina, Yuliya I.; Allué-Guardia, Anna; Eppinger, Mark; Riddle, Mark S.; Tribble, David R.; Johnson, Ryan C.; Dalgard, Clifton L.; Sukumar, Gauthaman; Connor, Patrick; Boisen, Nadia; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
To discern if there was a particular genotype associated with clinical enteroaggregative Escherichia coli (EAEC) strains isolated from deployed military personnel (DMP) with travelers' diarrhea (TD), we characterized a collection of EAEC from DMP deployed to Afghanistan, Djibouti, Kenya, or Honduras. Although we did not identify a specific EAEC genotype associated with TD in DMP, we found that EAEC isolated at the first clinic visit were more likely to encode the dispersin gene aap than EAEC collected at follow-up visits. A majority of the EAEC isolates were typical EAEC that adhered to HEp-2 cells, formed biofilms, and harbored genes for aggregative adherence fimbriae (AAF), AggR, and serine protease autotransporters of Enterobacteriaceae (SPATEs). A separate subset of the EAEC had aggR and genes for SPATEs but encoded a gene highly homologous to that for CS22, a fimbriae more commonly found in enterotoxigenic E. coli. None of these CS22-encoding EAEC formed biofilms in vitro or adhered to HEp-2 cells. Whole genome sequence and single nucleotide polymorphism analyses demonstrated that most of the strains were genetically diverse, but that a few were closely related. Isolation of these related strains occurred within days to more than a year apart, a finding that suggests a persistent source and genomic stability. In an ampicillin-treated mouse model we found that an agg4A+ aar- isolate formed a biofilm in the intestine and caused reduced weight gain in mice, whereas a strain that did not form an in vivo biofilm caused no morbidity. Our diverse strain collection from DMP displays the heterogeneity of EAEC strains isolated from human patients, and our mouse model of infection indicated the genotype agg4A+ aar– and/or capacity to form biofilm in vivo may correlate to disease severity.